Eigenfrequency shift of piezoelectric backplate in vibro-acoustic energy harvesting - Muhammad Hatifi, Mansor; M. S. M., Sani; Mohd Firdaus, Hassan (Universiti Malaysia Pahang, 2023)
Noise is increasingly recognised as a serious, worldwide public health concern. Noise is a type of occupational hazard that can cause damage to hearing and other health effects in workers who are exposed to high levels of noise in their work environment. Traditionally, noise can be controlled and suppressed but recently, noise can be useful and converted into electrical energy. The process of converting noise or acoustic waves into electrical energy by using a quarter wavelength resonator tube embedded with a flexible piezoelectric backplate was used in this study. The results show the maximum output voltage of 1.41 V/Pa at 112 Hz and 0.44 V/Pa at 225 Hz in the experiment, and 1.44 V/Pa at 106 Hz and 0.41 V/Pa at 226.5 Hz with incident sound waves at 90 dB. A parametric study was then performed by adjusting the lumped pointed mass at the piezoelectric backplate to tune the resonant frequencies of the system and the optimal power output. The point mass has given significant change in the acoustic properties. The maximum output power increased from 20.4 at 112 Hz using a flexible back plate to 711 at 119.75 Hz. Various small power applications can benefit from the approach by reducing and absorbing specific low-frequency bandwidths of continuous noise in the environment.